THE POSSIBILITY OF USING TIMBER FROM PLANTATION FOREST TREATED WITH PLASTIC AND CCB FOR MARINE CONSTRUCTION - Mohammad Muslich; Nurwati Hadjib (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2008)
Recently, timber estate or plantation forest plays an important role on wooden based industries. However, the plantation timber quality is relatively low. Some treatments have been developed to improve its low quality, such as preservation with CCB (Chromate Copper Boron) and impregnation with plastic compounds. This study is to compare the durability of timber treated with plastic and CCB, non-treated from plantation forest timber as well as from natural forest. The plantation timber studied were jeungjing (Paraserianthes falcataria), damar (Agathis sp.), pinus (Pinus merkusii), and rubberwood (Hevea brasilliensis). Non-treated timbers that usually used for marine construction were ulin (Eusideroxylon zwageri), jati/teak (Tectona grandis), laban (Vitex pubescens) and merbau (Instia bijuga). After 6 and 12 months, the results showed that CCB preserved timber were more durable than plastic impregnated timber and non- treated timber. Wood samples were mostly attacked by marine borer organisms from the family of Pholadidae and Teredinidae. The experiment results revealed the possibility of using those plantation forest timber species for marine construction purposes.